Synthetic SIGLEC9-based chimeric switch receptor augments the efficacy of CAR macrophages against glioblastoma - Zhipeng Fu; Xiaotian Zhao; Qikang Zhang; Maosen Han; Jing Zhang; Zhenmei Yang; Yan Wang; Zichao Yao; Ying Liu; Chunwei Tang; Kaiyan Xi; Zhanyan Liu; et al. (Proceedings of the National Academy of Sciences, 2026)
Chimeric antigen receptor macrophage (CAR-M) therapy represents a promising therapeutic approach for treating glioblastoma multiforme (GBM). However, durable antitumorigenic macrophage phenotype of CAR-Ms is limited by the highly immunosuppressive tumor microenvironment (TME), wherein Siglec–sialic acid signaling directly drives macrophage polarization toward a protumorigenic phenotype. We here report an in situ synthetic SIGLEC9-based chimeric switch receptor (CSR) for diverting the inhibitory signal into positive ones, augmenting the sustained proinflammatory phenotype and tumoricidal immunity of CAR-Ms in the GBM niche. Specifically, our results showed that macrophage-targeted ionizable lipid nanoparticles efficiently introduce dual circRNAs into macrophages to generate CSR functionalized CAR-Ms in vitro and in vivo. The modified macrophages maintained a proinflammatory state, exhibited superior phagocytic activity, resulting in rapid and efficient eradication of IL13Rα2-positive tumor cells. Moreover, an injectable nanoparticle–hydrogel system for reprogramming macrophages surrounding the glioma resection cavity initiated a locoregional antitumor immune response and elicited robust long-term immunological memory, inhibiting tumor relapse in the postoperative GBM model. In sum, our findings establish that the engineered SIGLEC9-based CSR significantly promotes the maintenance of an antitumoral phenotype of CAR-Ms in the hypersialylated acidic TME, contributing to the improvement of engineered macrophage-based immunotherapy against GBM.